PET and MRI show differences in cerebral asymmetry and functional connectivity between homo- and heterosexual subjects - Savic, Ivanka; Lindström, Per (Proceedings of the National Academy of Sciences - PNAS, 2008)
Cerebral responses to putative pheromones and objects of sexual attraction were recently found to differ between homo- and heterosexual subjects. Although this observation may merely mirror perceptional differences, it raises the intriguing question as to whether certain sexually dimorphic features in the brain may differ between individuals of the same sex but different sexual orientation. We addressed this issue by studying hemispheric asymmetry and functional connectivity, two parameters that in previous publications have shown specific sex differences. Ninety subjects [25 heterosexual men (HeM) and women (HeW), and 20 homosexual men (HoM) and women (HoW)] were investigated with magnetic resonance volumetry of cerebral and cerebellar hemispheres. Fifty of them also participated in PET measurements of cerebral blood flow, used for analyses of functional connections from the right and left amygdalae. HeM and HoW showed a rightward cerebral asymmetry, whereas volumes of the cerebral hemispheres were symmetrical in HoM and HeW. No cerebellar asymmetries were found. Homosexual subjects also showed sex-atypical amygdala connections. In HoM, as in HeW, the connections were more widespread from the left amygdala; in HoW and HeM, on the other hand, from the right amygdala. Furthermore, in HoM and HeW the connections were primarily displayed with the contralateral amygdala and the anterior cingulate, in HeM and HoW with the caudate, putamen, and the prefrontal cortex. The present study shows sex-atypical cerebral asymmetry and functional connections in homosexual subjects. The results cannot be primarily ascribed to learned effects, and they suggest a linkage to neurobiological entities.